Cellular reactions to three-dimensional matrices of polylactic acid and hydroxyapatite generated by 3D-printing - T. V. Druzhinina; S. Ya. Talalaev; N. P. Zakirov; S. V. Shchadenko; Sh. A. Khabibulin; I. A. Khlusov; L. S. Litvinova (Бюллетень сибирской медицины)
The purpose of this study is to estimate Ex vivo physicochemical and biological features of three-dimensional (3D) biodegradable matrices “polylactic acid/calcium phosphates” (hereafter 3D composites) designed with the help of additive technologies (3D printing) as potential materials for bone tissue regeneration.Materials and methods. Experimental samples (disks 1,2–1,6 mm thick, and 11 mm or 8 mm in diameter) of composite biodegradable 3D matrices (hereafter 3D composites) have been produced from initial mixture of 95 mas% polylactic acid (PLA) and 5 mas% hydroxyapatite (HAP). Computer-aided design method, Blender software and fused filament fabrication (FFF; fiber diameter 1,75 mm) with 3D printing were used in sample production. 100 mas% PLA disks served as control. One of the sample surfaces was textured with 0,3–0,5 mm wide grooves. Physicochemical properties of 11 mm disks (geometry, mass, morphology, roughness, electrostatic voltage, surface wettability, and element composition) were studied. Biological trials included the evaluation of 24-hour cytotoxicity of 8 mm samples in culture of mononuclear leukocytes of a healthy volunteer or human Jurkat T cell leukemia-derived cell line (hereafter Jurkat T cells). Moreover, osteogenic potential of 11 mm disks was determined in 21-day culture of human adipose-derived multipotent mesenchymal stem cells (AMMSCs) be means of osteocalcin secretion and intercellular matrix mineralization visualized by alizarin red S staining.Results. The features of PLA-HAP 3D composites generated by 3D printing correspond to physicochemical parameters which are crucial for bone tissue recovery. In case of small amount of calcium and phosphorus they facilitated ex vivo mineralization of extracellular matrix formed in AMMSCs culture. The number of died (by necrosis, mainly) leukemic Jurkat T cells but not mononuclear leukocytes of a health volunteer increased to 9–10% in 24-hour in vitro contact with PLA-HAP 3D composites unlike PLA samples alone.Conclusion. Polar reaction of tumor and normal cells to PLA-HAP samples in case of increasing amount of calcium phosphates in 3D-composite may be valuable for the development of new materials used for osteosynthesis of fractures and endoprosthesis in patients with hematological malignancies.